An advanced spectroscopic approach (LIBS in combination with AAS): a steadfast means to probe the elemental composition of monosodium glutamate. (4th June 2019) - Rehan, Imran; Rehan, Kamran; Khan, M Zubair; Farooq, Zahid; Haq, S U; Sultana, Sabiha; Rahman, M Ur; Mehmood, Faisal
Abstract: The elemental composition of monosodium glutamate (MSG) was probed by engaging a laser-induced breakdown spectroscopy (LIBS) analytical technique. The LIBS spectra of MSG were acquired in air pressure with an appropriate detector (LIBS2000  +  , Ocean Optics) with an optical resolution of ~0.06 nm in the spectral range from 220 to 720 nm. Analyses of the acquired LIBS spectra revealed the presence of Ag, Ca, Mg, S and Na in the sample. To maximize the signal to noise ratio in the resulting LIBS spectra, the experimental parameters, such as pulse energy and gate delay, were optimized. The accomplishment of local thermodynamic equilibrium supposition was confirmed by the McWhirter's criterion and in view of the relaxation time, as well as the diffusion length of the atoms in the plasma. For the determination of relative concentrations of detected elements in MSG, we used three LIBS-based approaches, i.e. by setting the concentration of Na as the calibration, by setting the sum of all concentrations as the calibration and by the calibration curve method. The same sample was also subjected to the more standard analytical tool of atomic absorption spectroscopy, and its results were cross-compared with the findings of LIBS to confirm its validity. It was highly encouraging to find that both results were in sound agreement.